Disruption of default mode network dynamics in acute and chronic pain states - Alshelh, Z.; Marciszewski, K.K.; Akhter, R.; Harrington, Flavia; Mills, E.P.; Vickers, E.R.; Peck, C.C.; Murray, G.M.; Henderson, L.A. (ELSEVIER SCI LTD, 2018)
© 2017 The Authors It has been proposed that pain competes with other attention-demanding stimuli for cognitive resources, and many chronic pain patients display significant attention and mental flexibility deficits. These alterations may result from disruptions in the functioning of the default mode network (DMN) which plays a critical role in attention, memory, prospection and self-processing, and recent investigations have found alterations in DMN function in multiple chronic pain conditions. Whilst it has been proposed that these DMN alterations are a characteristic of pain that is chronic in nature, we recently reported altered oscillatory activity in the DMN during an acute, 5 minute noxious stimulus in healthy control subjects. We therefore hypothesize that altered DMN activity patterns will not be restricted to those in chronic pain but instead will also occur in healthy individuals during tonic noxious stimuli. We used functional magnetic resonance imaging to measure resting state infra-slow oscillatory activity and functional connectivity in patients with chronic orofacial pain at rest and in healthy controls during a 20-minute tonic pain stimulus. We found decreases in oscillatory activity in key regions of the DMN in patients with chronic pain, as well as in healthy controls during tonic pain in addition to changes in functional connectivity between the posterior cingulate cortex and areas of the DMN in both groups. The results show that similar alterations in DMN function occur in healthy individuals during acute noxious stimuli as well as in individuals with chronic pain. These DMN changes may reflect the presence of pain per se and may underlie alterations in attentional processes that occur in the presence of pain.